SOLIDARITY VALUE IN EXTREME JOB FILM BY LEE BYUNG HUN - Shadiyah, Chalimatus; Novia Bahari, Jannatul Laily (Universitas Islam Lamongan, 2020)
Based on Korean Film Data, Extreme Job is a Korean action comedy film has become the second best-seller Korean film which is directed by Lee Byung Hun. Not only is the comedian's story interesting, this film also contains solidarity value. The problem in this study is how the representation of solidarity value through Extreme Job film by Lee Byung Hun? To elaborate the problem in depth, this study uses the method of semiotic analysis by Roland Barthes. The aim is to analyse the representation of solidarity value in Extreme Job film. Barthes's semiotic analysis, namely denotative and connotative. Denotation is the first step in system of signification. It explained shortly, densely, and clearly. Connotation is the second step in system of signification. It explained more extensively than denotation because connotation is liberal. On the significance of the first step is cohesion showed by the existence of togetherness on doing something, the persuasion is the result of their solidarity also as a reason in order to buy the chicken restaurant through altruism, and division police's jobs for investigating narcotic consumers to various places where destinated by delivers of chicken with narcotic. On the significance of the second step is cohesion as a solidarity indicated based on main purpose of police, recklessness of altruism that showed solidarity among job partners for make success their mission to chasing the group of narcotic fugitives, and job division sign that showed solidarity among job partners for arresting the group of narcotic fugitives.Â